Simple and Rapid Method by Ultra High-Performance Liquid Chromatography (UHPLC) with Ultraviolet Detection for Determination of Efavirenz in Plasma: Application in a Preclinical Pharmacokinetic Study - Dos Santos Martins, Evelin [UNESP]; Oliveira, Jonata Augusto [UNESP]; Franchin, Taísa Busaranho [UNESP]; Silva, Bruna Cristina Ulian [UNESP]; Cândido, Caroline Damico [UNESP]; Peccinini, Rosângela Gonçalves [UNESP] (Oxford University Press (OUP), 2019)
A simple and rapid ultra-high-performance liquid chromatography (UHPLC) method for determination of efavirenz (EFV) in plasma was developed and applied in a preclinical pharmacokinetic study. The method involves only addition of acetonitrile to precipitation of plasma proteins followed by solvent evaporation. The mobile phase consisted of methanol, acetonitrile and 0.1 M formic acid (20:50:30) at a flow rate of 0.3 mL/min with run time of 5 min. A CSH C18 column and a UHPLC-UV system operating at 245 nm were used. There was a linear response in the range of 0.078 to 10 μg/mL, and the equation was obtained by weighting (1/x2) with r2 = 0.9965. The pharmacokinetic disposition of EFV was investigated in rabbits (two groups, n = 7) following a single intravenous administration (IV group) at a dose of 2.7 mg/kg and a single oral administration (oral group) of EFV co-administered with lamivudine (3TC) and tenofovir (TNF) at a dose of 50, 25 and 25 mg, respectively. The study demonstrated the applicability of the method for determination of EFV in plasma without interference from other co-administered drugs, and the pharmacokinetic parameters were calculated. The method showed advantages over other methods in the literature, such as simplicity of sample processing and fast results.
Keywords: AIDS; Bioanalytical method; Efavirenz; Pharmacokinetics; UHPLC